Faktor-Faktor Yang Mempengaruhi Auditor Dalam Memberikan Opini Audit Going Concern Pada Masa Pandemi Covid-19 - Ningrum, Ayu Citra; Qintharah, Yuha Nadhirah (MIZANIA: Jurnal Ekonomi Dan Akuntansi, 2022)
This study aims to understand how influential the company's growth, financial disress, audit committee size and KAP reputation are on going concern audit opinions listed on the IDX for the 2020-20210period. The use of research data is taken on the website www.bursaelektroindonesia.com using secondary data. Then the method used in this research is using quantitative methods. The technique in selecting the sample in this research used purposive sampling technique, so that the total sample of companies in this research amounted to 50 entities with a total period of 2 years used so that the observations in this study amounted to 100 observations. The analysis in this research uses panel data regression and uses the application of SPSS version 23 The results of this research can then convey information that the company growth variable has a negative effect on going-concern audit opinion, Financial distress has a positive effect on going-concern audit opinion, and audit committee size has a negative effect on going concern audit opinion, and KAP reputation has a positive effect on going concern audit opinion.